(untitled) (CIPEEX, 2025)
Ligaments are essential for the passive stabilization of joints, and their integrity is crucial for the proper function of daily activities. Among knee injuries, anterior cruciate ligament (ACL) rupture is prevalent in physical and sports activities such as running, soccer, handball, and basketball, often resulting in knee injuries due to its supportive role. ACL rupture compromises joint stability and causes a sensation of "giving way" under weight-bearing. Lower limb injuries, particularly ACL injuries, are common in men aged 18 to 45 years. Thus, it is essential that we understand the characteristics of this population more prone to these injuries and how they occur. The objective of this study is to analyze the epidemiological profile of patients with anterior cruciate ligament (ACL) injury, identifying the main injury mechanisms and risk factors in individuals post-surgery at a reference hospital in the central-north region of Goiás. This study is cross-sectional and quantitative, conducted at an Orthopedic Hospital in rural Goiás, investigating the epidemiological profile of patients after ACL surgery. Coordinated by the Evangelical University of Goiás and ethically approved, the study focused on analyzing the demographic profile, injury mechanisms associated, and post-operative characteristics of adults (18-60 years) of both sexes. A digital questionnaire via Google Forms was used for data collection, which was analyzed using SPSS 2.0 to provide a detailed understanding of the post-surgical conditions of these patients. The study involved 27 participants with ligament rupture, with 22.2% women and 77.8% men, with an average age of 34 years, highlighting a significant predominance of cases among young adult men. It was observed that 76.92% of male participants were playing soccer at the time of injury. Most injuries occurred during sports activities (48.1%), followed by falls (18.5%) and accidents involving horses (14.8%). Car and motorcycle accidents accounted for 7.4% each, while work-related injuries represented 3.7% of cases. These data indicate that sports activities were the main cause of injuries, followed by falls and accidents involving horses, with most injuries occurring outside the workplace. Thus, these data highlight that sports activities are the primary cause of ACL ruptures, followed by falls and accidents involving horses, with the majority of injuries occurring outside the workplace.